iPSCs: from bench to clinical bed - Li, Yuging (2016)
Induced pluripotent stem cells (iPSC) have been acknowledged as a milestone in the field of stem cell biology and regenerative medicine, providing an excellent tool to tackle fundamental biological issues regarding reproduction, regeneration, and (de)differentiation at genetic and epigenetic levels, and the valuable cell sources for tissue regeneration, human disease modeling, and drug discovery. Furthermore, iPSC generation with patient-specific somatic cells holds great promise for autologous cell replacement therapy and organ transplantations.